2015
DOI: 10.3346/jkms.2015.30.6.793
|View full text |Cite|
|
Sign up to set email alerts
|

A U-shaped Association between Body Mass Index and Psychological Distress on the Multiphasic Personality Inventory: Retrospective Cross-sectional Analysis of 19-year-old Men in Korea

Abstract: Objective personality tests, such as the Minnesota Multiphasic Personality Inventory (MMPI), might be more sensitive to reflect subclinical personality and be more state-dependent in an individual's lifetime, so they are good scales to predict the psychological distress regarding certain states. The aim of this study was to identify the specific pattern between body mass index (BMI) and psychological distress using the objective personality test. For this study, we investigated BMI and the Korean Military Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“… 7 Moreover, girls and young women are particularly vulnerable to weight balance issues. 25 The results from previous large population-based studies that evaluated the relation between BMI and depression 23 26 27 and the relation between BMI and body dissatisfaction 6 are in accordance with our findings. Istvan et al 26 reported that BMI is related to depression in women but not in men, and Carpenter et al 27 found that underweight men and obese women experienced depression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 7 Moreover, girls and young women are particularly vulnerable to weight balance issues. 25 The results from previous large population-based studies that evaluated the relation between BMI and depression 23 26 27 and the relation between BMI and body dissatisfaction 6 are in accordance with our findings. Istvan et al 26 reported that BMI is related to depression in women but not in men, and Carpenter et al 27 found that underweight men and obese women experienced depression.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, higher BMI was related to body dissatisfaction 21 22 and to psychological distress. 23 As stated above, obese people are treated with unjust prejudice and discrimination, 7 8 which could be a chronic stressor and could adversely affect their face and body image. As obesity is becoming an increasing problem in westernized countries, social pressure for thinness also increases.…”
Section: Discussionmentioning
confidence: 99%
“…This was in contrast to most findings from Western studies, which have reported that clinical overweight or obesity is significantly associated with depression 31 32 33 34 . In addition, others have reported that both underweight and obesity are associated with depression, and a U-shaped relationship between depression and BMI has been described 35 36 . However, our findings are consistent with a previous study conducted in the Chinese elderly, which also demonstrated an inverse relationship between BMI and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the well‐established empirical regularity in the health literature that longevity increases monotonically in BMI up to 25, with BMI between 23 and 25 considered optimal for health (Fontaine et al, 2003; Whitlock et al, 2009; Kim et al, 2015; Ju et al, 2015), the study concludes that migration enhances, weakly, the health prospects of migrant senders with BMI less than 25, by increasing their average BMI by 0.6 from a baseline of about 22. Moreover, migration contributes to a recession in the health of senders who are in the overweight category, by raising their BMI by about 1.2.…”
Section: Introductionmentioning
confidence: 99%